Energy saving Mechanism in cloud computing by using multi core architecture (International Journal of Engineering and Computer Science, 2014)
Energy efficiency is more and more essential for upcoming information and communication technologies (ICT), for the reason that the enlarged usage of ICT, jointly with growing energy expenses and  require to decrease green house gas emissions call for energy-efficient technologies that reduce the overall energy utilization of computation, storage and communications. Cloud computing is becoming an opportunity for industry to permit a high level of communication expertise, scalability, and usability of computing resources. The optimization of Cloud computing has grows in the industry of huge-scale data centres over the globe have various nodes. We can keep energy by CPU Utilization and using DVFS, live migration of VM and virtualization by using multi –core architecture. This paper presents analysis of cloud computing features, issues and software for dynamic resource saving mechanism with Virtual Machines (VMs) and multi-core architecture is used to hold multi-virtual machines   in Cloud data centres.